Deterministic seasonality versus seasonal fractional integration - Luis A. Gil-Ala\~na (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2000)
We make use in this article of a testing procedure suggested by Robinson (1994) for testing deterministic seasonality versus seasonal fractional integration. A new test statistic is developed to simultaneously test both, the order of integration of the seasonal component and the need of seasonal dummy variables. Finite-sample critical values of the tests are computed and, an empirical application, using both, Robinson (1994) and the joint test described in the paper, is also carried out at the end of the article.
urn:nbn:de:kobv:11-10048326
Keywords: C12; C15; C22; 330; Long memory; Deterministic seasonality; Seasonal fractional integration